2023
DOI: 10.3389/fpubh.2022.1074017
|View full text |Cite
|
Sign up to set email alerts
|

Association between the risk of heart failure hospitalization and end-stage renal disease with digoxin usage in patients with cardiorenal syndrome: A population-based study

Abstract: BackgroundThe management of the coexistence of heart disease and kidney disease is increasingly challenging for clinicians. Chronic kidney disease (CKD) is not only a prevalent comorbidity of patients with heart failure but has also been identified as a noteworthy risk factor for all-cause mortality and poor clinical outcomes. Digoxin is one of the commonest treatments for heart disease. There are few trials investigating the role of digoxin in patients with cardiorenal syndrome (CRS). This study aims to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Since the DIG trial was published, various observational studies have shown increased mortality and hospitalisation rate with patients on digoxin compared to those not on digoxin in patients with HFrEF [ 150 , 151 ]. This is similarly shown in patients with advanced kidney disease [ 152 , 153 ]. The hypothesis regarding the difference in effect is that a prescription bias exists; digoxin is more often prescribed to patients with advanced HF in clinical practice, compared to in a RCT.…”
Section: Othersmentioning
confidence: 56%
“…Since the DIG trial was published, various observational studies have shown increased mortality and hospitalisation rate with patients on digoxin compared to those not on digoxin in patients with HFrEF [ 150 , 151 ]. This is similarly shown in patients with advanced kidney disease [ 152 , 153 ]. The hypothesis regarding the difference in effect is that a prescription bias exists; digoxin is more often prescribed to patients with advanced HF in clinical practice, compared to in a RCT.…”
Section: Othersmentioning
confidence: 56%
“…Furthermore, cardiovascular-related mortality makes up nearly half of deaths of people with chronic kidney disease [4]. Overall, co-occurrence of HF and kidney disease leads to an increased risk of mortality [3,[5][6][7][8][9] and may play an important role in therapeutic decision making [10]. The public health burden of these diseases is largely unabated and even increasing in younger adults [11,12].…”
Section: Introductionmentioning
confidence: 99%